2013
DOI: 10.1007/s11596-013-1138-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in platelet GPIbα and ADAM17 during the acute stage of atherosclerotic ischemic stroke among Chinese

Abstract: Glycoprotein (GP) Ibα ectodomain shedding has important implications for thrombosis and hemostasis. A disintegrin and metalloproteinase 17 (ADAM17) was identified to play an essential role in agonist induced GPIbα shedding. The relationship of GPIbα shedding and ADAM17 in the acute stage of atherosclerotic ischemic stroke (AIS) patients has not been thoroughly studied. A total of 306 patients and 230 controls matched for age, sex, race, history of hypertension and diabetes mellitus were enrolled in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The results of this study show that QEF can reduce bone resorption through the adjustment of VDR mRNA expression. This experiment uses stable and effective active vitamin D 3 reported in literatures as the reference drug for the control study [9]- [11]. Data shows similar drug efficacy between QEF and active vitamin D 3 , as both are able to increase VDR mRNA expression in the body in reducing bone resorption and strengthening the quality and quantity of bones.…”
Section: Discussionmentioning
confidence: 95%
“…The results of this study show that QEF can reduce bone resorption through the adjustment of VDR mRNA expression. This experiment uses stable and effective active vitamin D 3 reported in literatures as the reference drug for the control study [9]- [11]. Data shows similar drug efficacy between QEF and active vitamin D 3 , as both are able to increase VDR mRNA expression in the body in reducing bone resorption and strengthening the quality and quantity of bones.…”
Section: Discussionmentioning
confidence: 95%
“…However, a potential explanation for the lack of differentiation between GPIb receptor numbers is the postulated downregulation of GPIb receptors as a result of ectodomain shedding that is induced by platelet agonists during modulation of platelet function [ 22 ]. Indeed, a recent study of Chinese patients with atherosclerotic IS demonstrated lower expression levels of GPIb but higher levels of a disintegrin and metalloproteinase 17 (ADAM17), an enzyme that has been reported to play a major role in GPIb shedding [ 23 ].…”
Section: Discussionmentioning
confidence: 99%